2011
DOI: 10.1111/j.1469-0691.2010.03304.x
|View full text |Cite
|
Sign up to set email alerts
|

Nebulized hypertonic saline treatment in hospitalized children with moderate to severe viral bronchiolitis

Abstract: The objective of this study was to determine the efficacy and safety of frequently inhaled nebulized hypertonic saline (HS) in infants with moderate to severe bronchiolitis. One hundred and twenty-six infants were randomized to receive either nebulized 3% hypertonic saline (HS) or 0.9% normal saline (NS), but only 112 patients completed the whole study. Cough, wheezing, pulmonary physical signs, clinical severity scores and the hospital length of stay (LOS) were recorded. The wheezing remission time was 4.8 ± … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
132
4
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(145 citation statements)
references
References 18 publications
(23 reference statements)
8
132
4
1
Order By: Relevance
“…9,[11][12][13][14] Our results challenge the conclusions of the most recent Cochrane review of HS, 18 which suggests a potential benefit of HS. We believe this is partly attributed to the 2 to 3 times longer average LOS in the latter studies 9,[11][12][13][14] than in the studies in the United States and India. It is possible that HS has a greater effect when administered over a longer period of time than in an acute setting with a shorter LOS.…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…9,[11][12][13][14] Our results challenge the conclusions of the most recent Cochrane review of HS, 18 which suggests a potential benefit of HS. We believe this is partly attributed to the 2 to 3 times longer average LOS in the latter studies 9,[11][12][13][14] than in the studies in the United States and India. It is possible that HS has a greater effect when administered over a longer period of time than in an acute setting with a shorter LOS.…”
Section: Discussioncontrasting
confidence: 57%
“…[15][16][17] Initial studies using HS for infants hospitalized with bronchiolitis suggest decreased LOS and improved severity scores. [9][10][11][12][13][14] Those studies differed from this study by excluding infants with previous wheeze, administering study medications with bronchodilators, or study subjects having much longer mean LOS. 9,10,13,14 A 2013 Cochrane review of HS in bronchiolitis referencing the aforementioned studies suggested 3% HS given with bronchodilators may be considered a safe and effective treatment of infants with mild to moderate bronchiolitis.…”
Section: What This Study Addsmentioning
confidence: 97%
“…7 Since this review, additional studies have evaluated HS in infants with bronchiolitis: 1 in an ambulatory setting, 3 in an emergency department (ED), and 5 in hospitalized patients. 6,[8][9][10][11][12][13][14][15][16] All of these studies have shown a reduction in pulmonary severity scores and/or a trend toward reduced admission rates in the HS group. Of note, all investigations to date have shown HS to be safe, with no patients experiencing decreased oxygen saturation, apnea, or cyanosis after administration of the medication.…”
Section: Discussionmentioning
confidence: 99%
“…In a follow-up study, Luo et al 35 conducted a prospective, randomized, controlled trial to determine the efficacy and safety of 4 mL of inhaled nebulized hypertonic saline vs 4 mL of inhaled nebulized NS in hospitalized infants with moderate to severe bronchiolitis. The authors compared signs and symptoms, CSS, and LOS of infants in the hypertonic saline group with those of the NS group.…”
Section: Clinical Trials Evaluating Hypertonic Saline Use In Hospitalsmentioning
confidence: 99%